Cognitive Behavior Therapy pada Individu yang Mengalami Phobia Sosial - Lutfia Fausta; Alfi Purnamasari (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Social phobia is something that happens a lot today and needs special attention. In overcoming social phobia, it can be done with Cognitive Behavior Therapy therapy. The purpose of Cognitive Behavior Therapy (CBT) therapy is to see how the Cognitive Behavior Therapy (CBT) method can help change the behavior and cognition of individuals who experience social phobia. This research was conducted for approximately 1 month. The subjects in this study were adult individuals aged 23 years who experienced social phobia. The method of collecting data by researchers is through observation, interviews, and psychological tests. Psychological tests were given to the subjects in the form of cognitive tests, namely the Weschler Adult Intelligence Scale (WAIS), personality tests, namely the Graphic and Wartegg tests, as well as the Sack's Sentence Comletion Test (SSCT) inventory test and the Depression, Anxiety, and Stress Scale (DASS) tests. This study uses a quantitative approach with an experimental method using a single case pre-test post-test design. Researchers use Cognitive Behavior Therapy (CBT) techniques to change negative thoughts and behaviors into more positive thoughts and behaviors when in social situations, in order to reduce the symptoms of social phobia they have. The intervention was given to the subject in 3 sessions. The results of the intervention showed that there was a change in behavior before and after the intervention. Before being given the CBT intervention, the subject had an anxiety level from 0 to 100, which was rated at 80, but after the intervention the subject had a rating of 60. In addition, based on the comparison of the DASS test scores between pre-test and post-test, it also decreased. It was found that the anxiety score in the subject decreased from very severe to severe and although the decrease in score had not reached the normal stage, the score obtained had decreased.